An image processing approach towards classification of defects on printed circuit board - Ibrahim, Zuwairie (2007)
The areas of focus will be related to key and future technologies as well as highly demanding manufacturing technologies in the industrial fields of Electrical & electronics, Automotive, Energy and environment, Innovative IT, Basic metals & Materials, Machinery & equipments, Chemicals, Bio-Technology, Plastics, Oil and petroleum, Life Sciences, Wood, Food, Rubber, Agriculture engineering.